Capital inflows and asset prices: Evidence from emerging Asia - Peter Tillmann (Goethe University Frankfurt, Institute for Monetary and Financial Stability (IMFS), 2012)
The withdrawal of foreign capital from emerging countries at the height of the recent financial crisis and its quick return sparked a debate about the impact of capital flow surges on asset markets. This paper addresses the response of property prices to an inflow of foreign capital. For that purpose we estimate a panel VAR on a set of Asian emerging market economies, for which the waves of inflows were particularly pronounced, and identify capital inflow shocks based on sign restrictions. Our results suggest that capital inflow shocks have a significant effect on the appreciation of house prices and equity prices. Capital inflow shocks account for - roughly - twice the portion of overall house price changes they explain in OECD countries. We also address crosscountry differences in the house price responses to shocks, which are most likely due to differences in the monetary policy response to capital inflows.
urn:nbn:de:hebis:30:3-268712
Keywords: F32; F41; E32; 330; Capital Inflows; House Prices; Monetary Policy; Sign Restrictions; Panel VAR